Analisis Yuridis Terhadap Wanprestasi Dalam Perjanjian Pembiayaan Penjaminan Fidusia - Muhammad Jieny Mulyana; Tami Rusli; Okta Anita (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Even though creditors have a fairly large role in economic performance and guarantees in particular, the legal protection for creditors in fiduciary guarantee agreements is considered to be very weak and limited. This study aims to determine the extent of legal protection for creditors in order to achieve legal certainty in fiduciary guarantee agreements by examining theories, concepts, legal principles, and laws and regulations based on primary legal materials. This study uses normative and empirical legal research methods. Based on the research results, the form of default in the consumer financing agreement with a fiduciary guarantee in Decree Number 12/Pdt.GS/2022/PN Tjk, it was determined that Mr. Iwan Andi Yanuarta has defaulted. The Defendants violated the financing agreement with a fiduciary guarantee by committing an act of default. The judge's considerations in handling default cases in financing agreements with fiduciary guarantees in Decision Number 12/Pdt.GS/2022/PN Tjk are in accordance with the principles of justice. The defendant was proven to have violated Article 1238 of the Civil Code concerning Default and Article 1243 of the Civil Code concerning compensation and costs, resulting in serious legal consequences. The amount of compensation to be paid by the Defendants is Rp. 116,968,300.00.